Alternative scenarios of bioenergy crop production in an agricultural landscape and implications for bird communities. Issue 1 (8th February 2016) - Blank, Peter J.; Williams, Carol L.; Sample, David W.; Meehan, Timothy D.; Turner, Monica G.
Abstract: Increased demand and government mandates for bioenergy crops in the United States could require a large allocation of agricultural land to bioenergy feedstock production and substantially alter current landscape patterns. Incorporating bioenergy landscape design into land‐use decision making could help maximize benefits and minimize trade‐offs among alternative land uses. We developed spatially explicit landscape scenarios of increased bioenergy crop production in an 80‐km radius agricultural landscape centered on a potential biomass‐processing energy facility and evaluated the consequences of each scenario for bird communities. Our scenarios included conversion of existing annual row crops to perennial bioenergy grasslands and conversion of existing grasslands to annual bioenergy row crops. The scenarios explored combinations of four biomass crop types (three potential grassland crops along a gradient of plant diversity and one annual row crop [corn]), three land conversion percentages to bioenergy crops (10%, 20%, or 30% of row crops or grasslands), and three spatial configurations of biomass crop fields (random, clustered near similar field types, or centered on the processing plant), yielding 36 scenarios. For each scenario, we predicted the impact on four bird community metrics: species richness, total bird density, species of greatest conservation need (SGCN) density, and SGCN hotspots (SGCN birds/ha ≥ 2). Bird community metrics consistently increased with conversion of row crops to bioenergy grasslands and consistently decreased with conversion of grasslands to bioenergy row crops. Spatial arrangement of bioenergy fields had strong effects on the bird community and in some cases was more influential than the amount converted to bioenergy crops. Clustering grasslands had a stronger positive influence on the bird community than locating grasslands near the central plant or at random. Expansion of bioenergy grasslands onto marginal agricultural lands will likely benefit grassland bird populations, and bioenergy landscapes could be designed to maximize biodiversity benefits while meeting targets for biomass production.